Mutagenic effects induced by the attack of NO2 radical to the guanine-cytosine base pair - Cerón-Carrasco, José P.; Requena, Alberto; Zúñiga, José; Jacquemin, Denis (Frontiers in Chemistry, 2015)
We investigate the attack of the nitrogen dioxide radical (NO2) to the guanine-cytosine (GC) base pair and the subsequent tautomeric reactions able to induce mutations, by means of density functional theory (DFT) calculations. The conducted simulations allow us to identify the most reactive sites of the GC base pair. Indeed, the computed relative energies demonstrate that the addition of the NO2 radical to the C8 position of the guanine base forms to the most stable adduct. Although the initial adducts might evolve to non-canonical structures via inter-base hydrogen bonds rearrangements, the probability for the proton exchange to occur lies in the same range as that observed for undamaged DNA. As a result, tautomeric errors in NO2-attacked DNA arises at the same rate as in canonical DNA, with no macroscopic impact on the overall stability of DNA. The potential mutagenic effects of the GC-NO2 radical adducts likely involve side reactions, e.g., the GC deprotonation to the solvent, rather than proton exchange between guanine and cytosine basis.